Adsorption of gallic acid, propyl gallate and polyphenols from Bryophyllum extracts on activated carbon - García-Pérez, Pascual (Sci Rep, 2019)
The adsorption of gallic acid (GA) and propyl gallate (PG) on activated carbon (AC) was studied as a function of the AC mass and temperature. Clean first order behavior was obtained for at least three half-lives and the equilibrium was reached after ∼4 h contact time. An increase in the temperature (T = 20–40 °C) increases their adsorption rate constant values (k(1)) by 2.5 fold but has a negligible effect on the amount of antioxidant adsorbed per mass of AC at equilibrium. We also analyzed the adsorption process of polyphenols from Bryophyllum extracts and ca 100% of the total amount of the polyphenols in the extract were adsorbed when using 7 mg of AC. Results can be explained on the basis of the Freundlich isotherm but do not fit the Langmuir model. Results suggest that the combination of emerging in vitro plant culture technologies with adsorption on activated carbon can be successfully employed to remove important amounts of bioactive compounds from plant extracts by employing effective, sustainable and environmental friendly procedures.